WACANA RESISTENSI PEREMPUAN DALAM FILM LIKE & SHARE (2022): ANALISIS WACANA KRITIS SARA MILLS - Hakim, Arif Rohman; Edwar, Valentina Edellwiz; Fakhrunnisa, Ritma; Nabila, Atika Silma (Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2025)
This article analyses the construction of discourse in the film Like & Share directed by Gina S. Noer. This research is qualitative with Sara Mills' critical discourse analysis as the theoretical framework. theoretical framework. Based on the results of the analysis, it is found that the film Like & Share presents a discourse of women's resistance to patriarchal values & stereotypes in society. society. Like & Share presents a discourse of resistance by by presenting the position of female subjects who are subordinated by patriarchal values. patriarchal values. In addition, the early part of the film seems to agree with the concept of male gaze both at the visual level & in the film dialogue. The film's visuals emphasise on women's bodies while the dialogue presents women's perspectives on patriarchal values patriarchal values. The resistance discourse is then presented through the impact ofpatriarchal values to women & the dynamics of power relations that occur in Sara and Lisa's personal relationships. personal relationship between the characters Sara and Lisa. This strategy can be declared effective in presenting the concept of gender equality to readers. In addition to presenting resistance discourse, Like & Share also raises the discourse of women supporting women, which is presented through the relationship between Sara and Lisa.support women discourse which is presented through the relationship between Sara and Lisa.